Gestión administrativa y satisfacción laboral en la Municipalidad Distrital del Yavari área administrativa 2025 - Farroñay Pacaya, Solymar de Jesus (2025)
A descriptive and correlational study was conducted with a quantitative approach and a non-experimental cross-sectional design, based on the statistical analysis of data collected without manipulation of variables. The results showed high reliability in the variables, with Cronbach's Alpha coefficients of 0.916 for administrative management and 0.933 for job satisfaction. Likewise, a positive, direct, and significant correlation was identified between both variables, with a Spearman's Rho correlation coefficient of 0.926** and a two-tailed significance level of 0.000. These findings support the acceptance of the alternative hypothesis, confirming that efficient administrative management is closely linked to higher levels of job satisfaction. Therefore, improving administrative processes and practices can significantly contribute to the well-being and commitment of workers, favoring the development and organizational stability in the Yavarí District Municipality.